Effect of CO2 Concentration on Carbonic Anhydrase and Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase Expression in Pea. - Majeau, N. (1996)
The effect of external CO2 concentration on the expression of carbonic anhydrase (CA) and ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) was examined in pea (Pisum sativum cv Little Marvel) leaves. Enzyme activities and their transcript levels were reduced in plants grown at 1000 [mu]L/L CO2 compared with plants grown in ambient air. Growth at 160 [mu]L/L CO2 also appeared to reduce steady-state transcript levels for rbcS, the gene encoding the small subunit of Rubisco, and for ca, the gene encoding CA; however, rbcS transcripts were reduced to a greater extent at this concentration. Rubisco activity was slightly lower in plants grown at 160 [mu]L/L CO2, and CA activity was significantly higher than that observed in air-grown plants. Transfer of plants from 1000 [mu]L/L to air levels of CO2 resulted in a rapid increase in both ca and rbcS transcript abundance in fully expanded leaves, followed by an increase in enzyme activity. Plants transferred from air to high-CO2 concentrations appeared to modulate transcript abundance and enzyme activity less quickly. Foliar carbohydrate levels were also examined in plants grown continuously at high and ambient CO2, and following changes in growth conditions that rapidly altered ca and rbcS transcript abundance and enzyme activities.